Progress in research on rhodium (III) oxide or rhodium sesquioxide (Rh2O3) and rhodium (IV) oxide (RhO2) nanoparticles in cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management under synchrotron and synchrocyclotron rad - Heidari , Alireza; Hotz , Margaret; MacDonald , Nancy; Peterson , Victoria; Caissutti , Angela; Besana , Elizabeth; Esposito , Jennifer; Schmitt , Katrina; Chan , Ling-Yu; Sherwood, Francesca; Henderson , Maria; Kimmel , Jimmy (International Journal of Advanced Chemistry, 2022)
In the current research, progress in research on Rhodium (III) Oxide or Rhodium Sesquioxide (Rh2O3) and Rhodium (IV) Oxide (RhO2) nanoparticles in cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management under synchrotron and synchrocyclotron radiations. is investigated. The calculation of thickness and optical constants of Rhodium (III) Oxide or Rhodium Sesquioxide (Rh2O3) and Rhodium (IV) Oxide (RhO2) progress in research on Rhodium (III) Oxide or Rhodium Sesquioxide (Rh2O3) and Rhodium (IV) Oxide (RhO2) nanoparticles in cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management under synchrotron and synchrocyclotron radiations produced using sol–gel method over glassy medium through a single reflection spectrum is presented. To obtain an appropriate fit for reflection spectrum, the classic Drude–Lorentz model for parametric di–electric function is used. The best fitting parameters are determined to simulate the reflection spectrum using Lovenberg–Marquardt optimization method. The simulated reflectivity from the derived optical constants and thickness are in good agreement with experimental results.Progress in research on Rhodium (III) Oxide or Rhodium Sesquioxide (Rh2O3) and Rhodium (IV) Oxide (RhO2) nanoparticles in cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management under synchrotron and synchrocyclotron radiations.